A Brief Review of Non-invasive Monitoring of Respiratory Condition for Extubated Patients with or at Risk for Obstructive Sleep Apnea after Surgery - Zhang, Xuezheng; Kassem, Mahmoud Attia Mohamed; Zhou, Ying; Shabsigh, Muhammad; Wang, Quanguang; Xu, Xuzhong (Frontiers in Medicine, 2017)
Obstructive sleep apnea (OSA), is one of the important risk factors contributing to postoperative airway complications. OSA alters the respiratory physiology and increases the sensitivity of muscle tone of the upper airway after surgery to residual anesthetic medication. Additionally, the prevalence of OSA was reported to be much higher among surgical patients than the general population. Therefore, appropriate monitoring to detect early respiratory impairment in postoperative extubated patients with possible OSA is challenging. Based on comprehensive clinical observation, several equipment have been used for monitoring the respiratory conditions of OSA patients after surgery, including the continuous pulse oximetry, capnorgraphy, photoplethysmography (PPG), and respiratory volume monitoring (RVM). To date, there has been no consensus on the most suitable device as a recommended standard of care. In this review, we describe the advantages and disadvantages of some possible monitoring strategies under certain clinical conditions. According to the literature, the continuous pulse oximetry, with its high sensitivity, is still the most widely used device. It is also cost-effective and convenient to use but has low specificity and does not reflect ventilation. Capnography is the most widely used device for detection of hypoventilation but it may not provide reliable data for extubated patients. Even normal capnography can’t exclude the existence of hypoxia. PPG shows the state of both ventilation and oxygenation, but it’s sensitivity needs further improvement. RVM provides real-time detection of hypoventilation, quantitative precise demonstration of RR, TV and MV for extubted patients, but no reflection of oxygenation. Altogether, the sole use of any of these devices is not ideal for monitoring of extubated patients with or at risk for OSA after surgery. However, we expect that the combined use of continuous pulse oximetry and RVM may be promising for these patients due to their complementary function which need further study.